1983
DOI: 10.1161/01.cir.67.3.566
|View full text |Cite
|
Sign up to set email alerts
|

Importance of left atrial function in patients with myocardial infarction.

Abstract: SUMMARY Left atrial function was evaluated in patients with and without remote myocardial infarction. The simultaneous left atrial pressure recording and left atrial and left ventricular cineangiograms were obtained with a catheter-tip micromanometer. The pressure-volume curve of the left atrium was composed of an A-loop and a V-loop. The ratio of active atrial emptying to left ventricular stroke volume in patients with myocardial infarction was significantly larger than that in normal subjects (42 + 12% vs 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
1
12

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(137 citation statements)
references
References 22 publications
7
115
1
12
Order By: Relevance
“…These results were correlated with the fall in LA pressure (Basnight et al 1991). In MS LA function may be disrupted due to increased LA afterload (Matsuda et al 1983;Matsuzaki et al 1991). It has been shown that LA afterload and the mean LA pressure decreases following PMV (Stefanadis ) 1.67 ± 0.16 Systolic blood pressure (mmHg) 130 ± 9 Diastolic blood pressure (mmHg) 77 ± 5 Heart rate (beat/min) 74 ± 9 et al 1998).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These results were correlated with the fall in LA pressure (Basnight et al 1991). In MS LA function may be disrupted due to increased LA afterload (Matsuda et al 1983;Matsuzaki et al 1991). It has been shown that LA afterload and the mean LA pressure decreases following PMV (Stefanadis ) 1.67 ± 0.16 Systolic blood pressure (mmHg) 130 ± 9 Diastolic blood pressure (mmHg) 77 ± 5 Heart rate (beat/min) 74 ± 9 et al 1998).…”
Section: Discussionmentioning
confidence: 89%
“…Because it is well known that normal LA has a reservoir, conduit and pump function (Matsuda et al 1983;Matsuzaki et al 1991). On the other hand, percutaneous balloon mitral valvuloplasty (PMV) is a therapeutic option in selected patients with MS.…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…LA function is closely related to LV diastolic filling, therefore, indices of LA function may predict exercise capacity in patients with LV dysfunction. [6][7][8] LA volume and antero-posterior diameter measurements have been used for the evaluation of left atrial function. 9,10) The objective of the present study was to evaluate the correlation between LA function and exercise capacity in patients with heart failure.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20] LA dilatation is usually recognized on the M-mode and two-dimensional echocardiogram; ultrafast computerized tomography, magnetic resonance imaging and radionuclide methods have also been introduced to identify changes in LA volumes and functions. [21][22][23] In routine clinical practice, the most commonly used approach has been the manual tracing method, which includes tracing the LA inner surface on a two-dimensional echocardiographic window providing the best image of the LA.…”
Section: Discussionmentioning
confidence: 99%